(untitled) (Journal of Naval Architecture and Marine Engineering, 2024)
This study investigates the corrosion of steel reinforcement in concrete structures exposed to marine and high humidity environments, focusing on chloride-induced corrosion. Specimens were prepared with two different ternary blended concrete mixes. One mix contains cement replacement of 20% fly ash and 50% slag (termed as T1), while the other contains cement replacement of 20% fly ash and 8% silica fume (termed as T2). On the top surface of the specimens, different size reservoirs were attached, ranging from 5 cm to 15 cm. The reservoirs were filled with NaCl solution with 10% concentration. The electromigration method was employed to accelerate chloride transportation, and corrosion evolution was monitored using electrochemical impedance spectroscopy (EIS) and linear polarization resistance (LPR) techniques for a period of around 900 days. The results showed that the length of the solution reservoir significantly impacts the corrosion current readings. T2 specimens exhibited lower corrosion current values compared to T1 specimens with similar reservoir lengths, indicating superior corrosion resistance and durability. Electrochemical measurements provide valuable insights into corrosion behavior and mitigation effectiveness. This work emphasizes the importance of the reservoir lengths on different concrete mixes and demonstrates the effectiveness of electrochemical measurements in understanding long-term corrosion performance in reinforced concrete structures. Journal of Naval Architecture and Marine Engineering, 21(2), 2024, P: 195- 206